МЕТОДИКА ВЫДЕЛЕНИЯ СТРУКТУРНЫХ ЛИНИЙ В ПОДЛЕДНО-ПОДВОДНОМ РЕЛЬЕФЕ АНТАРКТИКИ - Ласточкин А.Н.; Попов С.В. (My University, 2004)
According to morphodynamic conception of geomorphology the determining of the ice bed surface structure should be the first stage in the investigation of subglacial-subaquatic relief of Antarctic. This structure is embodied in the net of structural lines: crest and keel lines, concave and convex kinks; it can be revealed visually or automatically on radar profiles and on hypso-bathymetric map showing subglacial-subaquatic relief. Three digital methods of distinguishing the structural lines were worked out: with the use of the observed profiles, with the use of the grid model of the surface and by means of the vector lines mapping and its further analysis. Precisely positioned structural lines may be widely used in geological and glaciological investigations.
Keywords: 551.4.012(99)